2008
DOI: 10.1021/es071519z
|View full text |Cite
|
Sign up to set email alerts
|

Methyl tert-Butyl Ether (MTBE) in Public and Private Wells in New Hampshire: Occurrence, Factors, and Possible Implications

Abstract: Methyl tert-butyl ether (MTBE) concentrations g0.2 µg/L were found in samples of untreated water in 18% of publicsupply wells (n ) 284) and 9.1% of private domestic wells (n ) 264) sampled in 2005 and 2006 in New Hampshire. In counties that used reformulated gasoline (RFG), MTBE occurred at or above 0.2 µg/L in 30% of public-and 17% of private-supply wells. Additionally, 52% of public-supply wells collocated with fuel storage and 71% of mobile home park wells had MTBE. MTBE occurrence in public-supply wells wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…These findings corroborate the results of a study of water supply wells in New Hampshire where 9.1% of private wells were found to contain detectable MTBE (Ayotte et al 2008). Ayotte et al (2008) conjecture that the MTBE releases were related to population density and undocumented (small) releases.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings corroborate the results of a study of water supply wells in New Hampshire where 9.1% of private wells were found to contain detectable MTBE (Ayotte et al 2008). Ayotte et al (2008) conjecture that the MTBE releases were related to population density and undocumented (small) releases.…”
Section: Discussionsupporting
confidence: 89%
“…These findings corroborate the results of a study of water supply wells in New Hampshire where 9.1% of private wells were found to contain detectable MTBE (Ayotte et al 2008). Ayotte et al (2008) conjecture that the MTBE releases were related to population density and undocumented (small) releases. The detection frequencies for MTBE in groundwater in Windham were similar, but not identical, to a study in Germany that found MTBE occurrences of 63% and 24% for urban and nonurban areas, respectively (Kolb and Puttmann 2006).…”
Section: Discussionsupporting
confidence: 89%
“…To date, MTBE-related problems have spread *Corresponding Author Email: jchen@zjut.edu.cn Tel. : +86571 8832 0386;Fax: +86571 8832 0882 worldwide including USA, Europe and Asia (Squillace et al, 1996;Achten and Puttmann, 2000;Hsieh et al, 2006;Ayotte et al, 2008). Therefore, there has been a growing concern regarding the treatment of MTBE contaminated groundwater in recent years (Suidan et al, 2005;Chen et al, , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…The question addressed in this study is, in the time since the discontinuation of MtBE usage, are widespread, low-levels of MtBE contamination in ambient groundwater changing, and can groundwater age explain these changes? Studies in areas with widespread, low-levels of MtBE completed shortly after the decline in MtBE use have been inconclusive (Ayotte et al, 2008;Peckenham, 2007). MTBE also is a concern internationally, although the rise and decline in its use may have been more rapid in the U.S. than elsewhere.…”
Section: Introductionmentioning
confidence: 99%